ANALYSIS OF STUDENT SKILLS IN BASIC ACCOUNTING EQUATIONS BASED ON COMPARISON OF LEARNING STRATEGIES AND PERSONALITY OF STUDENTS AT MAN 1 CITY OF GORONTALO - Selfia Bilondatu,; Usman Moonti,; Niswatin,; Fahrudin Zain Olilingo,; Radia Hafid, (International Journal of Innovations in Engineering Research and Technology, 2023)
Study This aim For analyze Skills students on the material equality base accountancy based on comparison of learning strategies and personality students at MAN 1 Gorontalo City. Approach in study This ie quantitative with method experiment . Deep data source study This is the primary data through deployment questionnaires , tests and observations . Amount sample in study This as many as 63 people namely 32 people for class XI IPS-1 and 31 people for class XI IPS-2. Data analysis technique used is Anova 2x2 and Independent Samples t Test with SPSS version 21 assistance . Research results This show that (1) exists significant difference from Skills students on the material equality base taught accounting using learning strategies based project with learning strategies based problems (PBL) in class XI IPS MAN 1 Gorontalo City (87.0000 > 79.5161). (2) Interaction of learning strategies based project ( PjBL ) with personality influential significant to Skills students on the material equality base accounting in class XI IPS MAN 1 Gorontalo City with mark determinant by 19.40%. (3) There is significant difference from Skills students on the material equality base taught accounting using learning strategies based project ( PjBL ) with learning strategies based problem (PBL) in students who have personality extrovert in class XI IPS MAN 1 Gorontalo City (86.8333 > 79.6875). (4) There is significant difference from Skills students on the material equality base taught accounting using learning strategies based project ( PjBL ) with learning strategies based problem (PBL) in students who have Introvert personality in class XI IPS MAN 1 Gorontalo City (87.1000 > 79.3333).